Application of WO3 Hierarchical Structures for the Detection of Dissolved Gases in Transformer Oil: A Mini Review - Wei, Zhijie; Xu, Lingna; Peng, Shudi; Zhou, Qu (Frontiers in Chemistry, 2020)
Oil-immersed power transformer has been considered as one of the most crucial and expensive devices in power system. Hence, high-performance gas sensors have been extensively explored and widely used for detecting the fault characteristic gases dissolved in transformer oil to evaluate the working state of transformer and thus ensure reliable operation of power grid. Hitherto, as a typical n-type metal-oxide semiconductor, Tungsten trioxide (WO3) has received considerable attention due to its unique structure. However, increasing requirements were proposed to detect the fault characteristic gases. Based on this, considerable efforts have been made to design and fabricate more prominent WO3 based sensors with higher responses and more outstanding properties. Lots of research focused on the synthesis of WO3 nanomaterials with different effective and controllable strategies. Meanwhile, the various morphologies of currently synthesized nanostructures from 0-D to 3-D are discussed with respective beneficial characteristics. Besides, this paper focused on the gas sensing properties and mechanisms of the WO3 based sensors, especially in the detection of the fault characteristic gases. In all, the detailed analysis above has contributed some beneficial guidance to the exploration on the surface morphology and special hierarchical structure of WO3 for high sensitivity detection of the fault characteristic gases in oil-immersed transformer.